2004
DOI: 10.1038/sj.onc.1207508
|View full text |Cite
|
Sign up to set email alerts
|

LMW-PTP is a positive regulator of tumor onset and growth

Abstract: Low molecular weight protein tyrosine phosphatases (LMW-PTPs) are an enzyme family that plays a key role in cell proliferation control by dephosphorylating/ inactivating both tyrosine kinase receptors (such as PDGF, insulin, and ephrin receptors) and docking proteins (such, as b-catenin) endowed with both adhesion and transcriptional activity. Besides being a frequent event in human tumors, overexpression of LMW-PTP has been recently demonstrated to be sufficient to induce neoplastic transformation. We recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 40 publications
3
91
0
4
Order By: Relevance
“…34 Alternatively, the phosphotyrosine content of EphA2 may also be negatively regulated by associated phosphatases such as LMW-PTP. 35, 36 The effect of EphA2 overexpression was examined in breast cancer by Zelinski and colleagues 9 who demonstrated that EphA2 overexpression was sufficient to confer malignant transformation and tumorigenic potential on non-transformed (MCF-10A) mammary epithelial cells. Nasreen and colleagues reported that EphA2 overexpression significantly enhanced the proliferation and haptotaxis of malignant mesothelioma cells.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…34 Alternatively, the phosphotyrosine content of EphA2 may also be negatively regulated by associated phosphatases such as LMW-PTP. 35, 36 The effect of EphA2 overexpression was examined in breast cancer by Zelinski and colleagues 9 who demonstrated that EphA2 overexpression was sufficient to confer malignant transformation and tumorigenic potential on non-transformed (MCF-10A) mammary epithelial cells. Nasreen and colleagues reported that EphA2 overexpression significantly enhanced the proliferation and haptotaxis of malignant mesothelioma cells.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…1 These cells provide growth factors, cell-to-cell interaction, and matrix proteins that play an important role in the regulation of haematopoiesis, and many of these cells may be derived from a common precursorthe mesenchymal stem cell (MSC). 2,3 It is therefore that the MSC population may serve as a facilitator of haematopoietic engraftment in clinical haematopoietic stem cell transplantation 4 as well as a good springboard for further studies of how stroma influences haematopoiesis. 5 It is currently recognized that the microenvironment in which a cancer cell grows comprises a critical component of the malignant disease process.…”
Section: Case Discussionmentioning
confidence: 99%
“…Although not well characterized in chronic lymphocytic leukemia, overexpression of LMWPTP is generally associated with a proliferative phenotype. 4 LMWPTP has been shown to interact with several tyrosine kinases including the platelet-derived growth factor receptor, the macrophage colony-stimulating factor receptor, the insulin receptor, the Eph receptor, and the epidermal growth factor receptor. 5 Since LMWPTP also interacts with Zap-70, 3 we followed the expression of activated Zap-70 and LMWPTP in a patient with chronic lymphocytic leukemia.…”
mentioning
confidence: 99%
“…Eukaryotic LMW PTPs play an important role in signal transduction mainly by specifically dephosphorylating and downregulating tyrosine kinase receptors such as the PDGF receptor or insulin receptor [37]. In S. cerevisiae heterologous overexpression of a LMW-PTP, Stp1, (from Schizosaccharomyces pombe) resulted in a large number of phenotypes that indicated down-regulation of the Ras pathway [38].…”
Section: Physiological Effects Of Sco3700 Overexpressionmentioning
confidence: 99%
“…Comparison of physiological behavior of the ptpA and sco3700 over expression strains and possible regulatory effects Dephosphorylation of proteins can mediate both activation and inactivation of target proteins, and by consequence physiological functions [37]. Overexpression of ptpA and sco3700 affected antibiotic production in S. coelicolor differently.…”
Section: Physiological Effects Of Sco3700 Overexpressionmentioning
confidence: 99%